Representasi Ideologi Pada Wacana Konflik Sosial Politik Dalam Teks Media Massa Kajian: Analisis Wacana Kritis Model Teun A. Van Dijk - Pelangi, Inne (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to reveal the representation of ideology in the discourse of socio-political conflict in mass media texts, especially in news texts regarding the polemic of the hashtag Ganti Presiden. This study aims to describe ideology in the superstructure, macrostructure, and microstructure of the discourse of socio-political conflict in mass media texts. The benefits of this study are: (1) It can provide theoretical contributions to critical discourse studies, especially regarding superstructure, macrostructure, and microstructure using the Teun A. van Dijk model. (2) For readers and further researchers, they can gain new insights and understanding of van Dijk's study in the discourse of socio-political conflict in the mass media and as reference material or references for further research. The method used in this study is descriptive qualitative with the techniques and strategies of critical discourse analysis of the Teun A. van Dijk model. The data sources in this study come from two daily newspapers, namely Tribun Timur and Fajar, published in Makassar. The results of the study show that there are three aspects in the critical discourse analysis model of Teun A. van Dijk, namely the super structure consisting of the beginning, middle, and end, the macro structure consisting of actors, events, and groups, and the micro structure consisting of experiential sentences, relational sentences and word choices.